2021
DOI: 10.1021/acsami.1c12683
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Manipulation of the Exchange Bias in a Pt/Co/NiO Structure

Abstract: An experimental study of the phenomenon of electric current influence on the value and orientation of the exchange bias field (H EB) in the Pt/Co/NiO structure is carried out. Depending on the direction of the magnetization in a ferromagnet (FM) layer and the current pulse amplitude, the value of the H EB field can be changed repeatedly in the range of ±7.5 mT. A few experiments are performed to separate the contributions from two current-induced effects: (i) an injection of the spin current into an antiferrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…36 It was found that in our Pt/Co/NiO devices, the temperature increased with applied voltage up to a critical temperature T crit of 335 K (see Supporting Information Figure S6), at which the RESET occurs. This value is far below the reported T N of a thin-film NiO (435−473 K) 25,43 and/or bulk NiO (∼525 K). 23 Based on these considerations, we can exclude the Joule heating effect from the mechanism that controls the EB through resistive switching.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…36 It was found that in our Pt/Co/NiO devices, the temperature increased with applied voltage up to a critical temperature T crit of 335 K (see Supporting Information Figure S6), at which the RESET occurs. This value is far below the reported T N of a thin-film NiO (435−473 K) 25,43 and/or bulk NiO (∼525 K). 23 Based on these considerations, we can exclude the Joule heating effect from the mechanism that controls the EB through resistive switching.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, the use of metallic spin sink layers is generally discouraged due to the potential increase in energy consumption resulting from current shunting. Recently, antiferromagnetic insulators have gained attention for their capabilities in high-efficiency, electron-free spin current transmission. Within this context, the insulating NiO film, with a high bulk Néel temperature of over 500 K, emerges as a notable candidate in spintronics. , Magnon-mediated magnetization switching was achieved with remarkable efficiency in the all-oxide heterostructure of SrRuO 3 /NiO/SrIrO 3 . Specifically, by inserting an insulating NiO layer within an in-plane magnetized Pt/NiO/CoFeB structure, the SOT efficiency of Pt can be significantly enhanced, potentially reaching the upper limit of the spin Hall angle.…”
Section: Introductionmentioning
confidence: 99%
“…EB has been realized in a variety of systems, including nanoparticles, epitaxial films, and polycrystalline films. [8][9][10][11] The establishment of EB usually involves cooling (or growing) the FM/AFM heterostructure from an elevated temperature higher than the Néel temperature in the presence of a static bias magnetic field, resulting in uniform EB of the device elements on a wafer level. However, with the increasing demand in terms of integration and scalability of the devices, localized manipulation of EB becomes desirable for design and optimization of various spintronic devices.…”
Section: Introductionmentioning
confidence: 99%